VD_FINDINFO Jug / 2016 / 134 vom 2. Dezember 2015 - VD Tribunal cantonal (2015)
REJET DE LA DEMANDE, AUTORISATION DE TRAVAIL, ERREUR DE DROITDROIT PÉNAL, PEINE PÉCUNIAIRE | 106 CP, 21 CP, 34 al. 1 CP, 42 al. 4 CP, 117 al. 1 LEtr, 91 al. 1 LEtr